Relationship on Three Factors Self Efficacy, Self-Actualization, and Working Environment with Heutagogy - Wardhani, Christova Hesti; Bambang Budi Wiyono; Zulkarnain; Hardika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Training for adults requires different ways and techniques in the application of special techniques that involve learning facilitators. An effective facilitator must have knowledge and competence about the content they teach, as well as skills to control the group. This leads to the need that the facilitator needs personal qualities that not only reflect the professionalism and character of the facilitator but also be able to overcome problems that occur in adult learning. This also happened at the Balai Besar Pemerintahan Desa Kementerian Dalam Negeri (BBPD) in Indonesia, which has the task and responsibility of conducting learning and training for village officials throughout Indonesia. Officials who are generally adult learners and have busy schedules need a reliable facilitator in the learning process. One of the things is to apply heutagogy as an alternative solution to maintain the facilitator's ability in adult learning. The application of heutagogy is expected to make the learning process lead to a sustainable system because they can return to their hometown with the expected application of knowledge. Based on the results of the preliminary analysis from the initial survey include the need for correct self-efficacy and the existence of a well-considered working environment also self-actualization in order to work more optimally in the learning process of adult learning using heutagogy. However, this needs to be proven empirically by quantitative research in more depth in the scope of BBPD so that the research result can state the validity of these three variable factors to the adult learning process carried out by BBPD. This research is explanatory research, which is research that seeks to explain the causal relationship that occurs between research variables and test hypotheses that have been formulated with quantitative research methods. The result shows that self-efficacy has the most significant factor among other aspects.